On the Issue of the Activities of the Polish Youth Organization «Corporation» in Right-bank Ukraine(1890 – 1904) - Stefaniia Bazhenova (Науковий вісник Чернівецького національного університету імені Юрія Федьковича. Історія, 2019)
Among the problems that are insufficiently studied in historical science remains the life of the Polish community inRight-Bank Ukraine in the 1890s – early 20th centuryin terms of its opposition to the imperial policy of demonopolization and Russification, the activities of youth opposition organizations, in particular the Polish student «Corporation», formed in Kyiv in the early 1890s, the main purpose of which was to fight against autocracy for the freedom of speech, assembly, to protect their rights and, as a final result, to prepare the fighters for the independence of Poland.